The impact of applications of sugar cane filter cake and vinasse on soil fertility factors in fields having four different crop rotations practices in Brazil - Campiteli, Livia Lima [UNESP]; Santos, Roberta Mendes [UNESP]; Lazarovits, George; Rigobelo, Everlon Cid [UNESP] (UNESP - Universidade Estadual Paulista, 2018)
In this study we examined how the use of vinasse and filter cake as fertilizers at four different sites alters crop yields of sugarcane. The objective was to determine the impacts based on the products fertility and to identify if and how the treatments altered soil microbiology. Using an untreated site as a control (treatment 1) we compared the effect on various soil parameters at sites where soybean was planted after cane production (treatment 2) using just chemical fertilizer, a site which received vinasse as a fertilizer during the sugarcane crop at levels that allowed for replacement of chemical K2O (treatment 3) and a site which received filter cake as a replacement of P2O5 (treatment 4). When all four sites were compared, organic matter was highest at sites amended with filter cake (19.8%) whereas, moisture levels were highest at the vinasse treated sites (18.9%). The phosphorus concentration was also the highest with filter cake amendment. The yields of sugarcane from the control and above described treatments did not differ each other. These findings suggest that vinasse and filter cake improve soil microbiological and fertility conditions although the changes here were not reflected in the yields of sugarcane crop obtained.
Keywords: Soil bacteria; Soil microbiology; Sugarcane